A savage song : Racist violence and armed resistance in the early twentieth-century U.S.-Mexico Borderlands - Aragon, Margarita (Sociologist) (Book collections on Project MUSE., 2021)
This book examines key moments of violent social unrest in the twentieth century United States. Investigating the centrality of constructions of gender to American racism, it asks how African and Mexican American men, including those in uniform, responded to the violence of racism, and how their resistance, including their claims to manhood and nation, were understood by law enforcement, politicians, and press.